Neurophysiological predictors of gaze-contingent music reward therapy among adults with social anxiety disorder. (November 2021) - Umemoto, Akina; Cole, Sally L.; Allison, Grace O.; Dolan, Sarah; Lazarov, Amit; Auerbach, Randy P.; Schneier, Franklin
Abstract: Social anxiety disorder (SAD) is associated with fear of negative evaluation and heightened performance monitoring. The best-established treatments help only a subset of patients, and there are no well-established predictors of treatment response. The current study investigated whether individual differences in processing errors might predict response to gaze-contingent music reward therapy (GC-MRT). At baseline, healthy control subjects (HC; n = 20) and adults with SAD (n = 29), ages 19–43 years, completed the Flanker Task while electroencephalography (EEG) data were recorded. SAD participants then received up to 12 sessions over 8 weeks of GC-MRT, designed to train participants' attention away from threatening and toward neutral faces. Clinical assessments were completed 9- (post-treatment) and 20-weeks (follow-up) after initiating the treatment. At baseline, compared to HC, SAD performed the task more accurately and exhibited increased error-related negativity (ERN) and delta power to error commission. After controlling for age and baseline symptoms, more negative ERN and increased frontal midline theta (FMT) predicted reduced self-reported social anxiety symptoms at post-treatment, and FMT also predicted clinician-rated and self-reported symptom reduction at the follow-up assessment. Hypervigilance to error is characteristic of SAD and warrants further research as a predictor of treatment response for GC-MRT. Highlights: Adults with social anxiety disorder made fewer errors relative to healthy adults. Socially anxious adults exhibited increased ERN and delta following commission errors compared to controls. Increased ERN and FMT power predicted reduced anxiety symptoms following GC-MRT treatment.